Development of encyclopedia based on local vegetables North Kayong Regency as biology learning media - Saripa Aini; Anandita Eka Setiadi; Ari Sunandar (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
The people of North Kayong Regency-West Kalimantan still uphold the culture of utilizing plants as food, known as North Kayong local vegetables. Preserving knowledge about existing local potential and its utilization can be done through education based on local wisdom or local potential. It can be employed as a tool to enhance the efficacy and significance of education while preserving the unique possibilities of every area. The K13 curriculum is a curriculum of change from conceptual learning to contextual learning. The education process according to regional potential can be done through encyclopaedia media that attracts readers because the encyclopedia contains explicit information and is accompanied by pictures with bright colours. analysis and development, the creation of a local vegetable-based encyclopedia of North Kayong Regency as a biology learning media using a development model (D&D) consisting of six stages, namely: problem identification, description of objectives, design and development, product trials, evaluation of trial results, and communication of trial outcomes. The outcomes of validation and students response trials to the encyclopedia media developed obtained perfect scores. Where the validation test received a value from media experts of 97.08% (very valid), material experts of 90.22% (very valid), and language experts of 88.14% (very valid). Students responded very well to the small-scale (78.83%) and large-scale (84.47%) trials.